Stroke unit and Neurocritical Care Unit for acute neurological diseases in the USL Toscana Centro: a pilot model of Santo Stefano Hospital in Prato - Valenti, Raffaella; Caruso, Alba; Scotto Di Luzio, Anita E.; Accavone, Donatella; Cagliarelli, Maria G.; Chiti, Guido; Grassi, Enrico; Briccoli Bati, Maria; Palumbo, Pasquale (Frontiers in Stroke, 2023)
Background: Acute neurological disease are important cause of disability and death. The need for specialist neurocritical care skills for managing neurological emergencies has increased. Promising opportunities exist to improve outcomes in acute phases of neurological diseases, as, for example, the concept of Stroke Unit for stroke patients. Similar concept was introduced for Neurocritical Care Unit, that are associated with improved clinical outcomes compared with more traditional management. Anyway, Neurocritical Care is often not recognized as a separate specialty. Significant progresses in neurology have enabled better approaches for the critically ill neurologic patient, in particular with stroke and haemorrhage, but also with epileptic seizures and epileptic status, traumatic brain injury, subdural/epidural hematoma, acute inflammatory polyradiculoneuritis, encephalitis, myasthenia gravis, acute myelitis, etc. Assessment of policy/guidelines options and implications Except for cerebrovascular diseases, for other acute neurological diseases, there is no standardized model care service recognized. A good patient outcome can be obtained by the choice of neurology setting for acute patients including nursing and medical staff with specific training in neurocritical care. As we believe neurocritical care practices should be implemented, we suggest a pilot model on the basis of our experience. In this report, we showed a model of Stroke Unit/Neurocritical Care (2A setting) of Santo Stefano Hospital (Prato, USL Toscana Centro), where, as well as Stroke Units for cerebrovascular events, we have carry out Neurocritical Care Units and acute-expert-neurologists for all acute neurological diseases. Actionable recommendations: our pilot experience The 2A setting of Stroke Unit/Neurocritical Care of Santo Stefano Hospital includes 15 beds; 8±2 beds are monitored by portable multi-parameter monitoring devices. Following acute treatment, diagnostic/aetiologic work-up and automated monitoring of vital functions are performed in addition to adapted secondary prevention, early rehabilitation and prevention of complications in all acute patients. We retrospectively assessed diagnoses in hospital discharge forms (HDF) of Stroke Unit/Neurocritical Care (2A) of 249 patients consecutively analysed between 1st January 2022 and 30th June 2022. Out of 249 patients affected by acute neurological diseases, 155 had cerebrovascular diseases (62.2%). In particular, 100 (64.5%) were diagnosed as ischemic stroke and 44 (28.4%) as hemorrhagic stroke [Figure 1].